Effect of wheel size on performance in elite cross-country mountain bikers - Steiner, T.; Müller, B.; Maier, T.; Wehrlin, J. P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: With the appearance of mountain bikes with 29-inch wheels (29er), debate arose among elite mountain bikers regarding the benefits compared to the traditional bike with 26-inch wheels (26er). While the 26er is usually lighter, stiffer, and is said to be easier to accelerate, it is assumed that the 29er offers lower rolling resistance, better traction, and a higher riding smoothness. So far, the bike choice has been made subjectively by every rider, depending on the course. The aim of the present study was to analyse the effect of different wheel sizes on performance on a simulated cross-country course to objectify the decision-making for the athletes. Methods: Power output (Powertap, Madison, USA), time and average heart rate (HR) were recorded for 11 Swiss National Team mountain bikers (8 male, 3 female) when riding two laps (total 1230 m, ascent 28 m) on a specially-built cross-country course. It consisted of two separate sections, assumed to favour the 29er (348 m) and 26er (267 m), respectively. All athletes completed 6 heats with 35 min of active recovery in between. Three heats were performed with their own 26er (bike weight including Powertap: 9.3 ± 0.6 kg) and 3 heats with their 29er bike (10.1 ± 1.0 kg). Five athletes started with the 26er and six athletes with the 29er. The bike was changed for every heat and athletes received no feedback on performance throughout the procedure. Paired t-tests were used to identify differences between the two wheel sizes. Results: Athletes were faster (p < 0.01) with the 29er (302 ± 25 s) than with the 26er (309 ± 28 s) while having a nearly identical (p = 0.96) power output (29er: 264 ± 46 W; 26er: 264 ± 45 W). No difference (p = 0.94) was observed for average HR between the two wheel sizes (29er: 174 ± 10 bpm; 26er: 174 ± 11 bpm). The 29er was also faster (p < 0.01) when sections were analysed separately, while no differences in power output were observed. All athletes had their fastest heat on the 29er. Discussion: The 29er seems to be superior to a 26er for elite mountain bikers, even on course-sections supposed to favour 26er bikes. It is emphasized that also athletes who trained considerably less on the 29er prior to the study took advantage of the bigger wheels. Whether these findings are limited to the short course used in this study cannot be concluded definitely. However, it can be assumed that, due to the reduced workload (same power output but faster times for a given distance), athletes will benefit even more from a 29er during cross country competitions usually lasting 100-135 min (Impellizeri et al., 2007).